Position specific physical performance and running intensity fluctuations in elite women`s football - Winther, A. K.; Baptista, I.; Pedersen, S.; Randers, M. B.; Johansen, D.; Krustrup, P.; Pettersen, S. A. (Scandinavian Journal of Medicine & Science in Sports, 2022)
The purpose of the present study was to investigate the physical performance of elite female football players during match play along with transient alterations in running performance following 1- and 5-min univariate peak periods. 54 elite female players from four top-level Norwegian teams were monitored for one season (n = 393 match observations), and physical performance data collected using STATSport GPS APEX. Results revealed significant differences in physical performance between the positions during full match play, particularly between wide and central players. Both full backs (FBs) and wide midfielders (WMs) covered more total distance (TD), high-speed running distance (HSRD), and sprint distance (SpD) than center backs (CBs) (p < 0.05-0.001), while WMs also covered more HSRD than both central midfielders (CMs) (p < 0.01) and forwards (FWs) (p < 0.05), and more acceleration -and deceleration distance (Accdist and Decdist) than both CBs and CMs (p < 0.01-0.001). A similar pattern was observed for the peak period analysis, with FBs and WMs covering more SpD in peak 1 min than CBs and CM (p < 0.001) and more SpD in peak 5-min than CBs, CMs, and FWs (p < 0.001). Irrespective of the variable analyzed, greater distances were covered during the peak 5-min period than in the next-5 and mean 5-min periods (p < 0.001). Significant (p < 0.001), but small to trivial (Cohen's Dz: 0.07-0.20), decreases in distance covered were also observed for each variable following each univariate peak 5-min period. In conclusion, practitioners should account for differences in physical performance when developing training programs for female football players and be aware of transient reductions in physical performance following univariate peak 1- and 5-min periods. Specifically, the very high intensity in 1-min peak periods adds support to the principal of executing speed endurance activities during training to mirror and be prepared for the physical demands of match play.